GLOBAL SCIENTIFIC-ARTISTIC INTERPRETATION AND STRUCTURAL ANALYSIS - Suvon Meli (Scholar Express Journal, 2022)
This article discusses what to rely on most when analyzing a work of art. In addition, an attempt was made to reveal the essence of the article through the method of structural analysis.
Keywords: method; structural analysis; interpretation; meaning